Few-shot learning-based human activity recognition. (30th December 2019) - Feng, Siwei; Duarte, Marco F.
Highlights: We propose a novel few-shot learning scheme for human activity recognition. We propose a general framework to measure cross-domain class-wise relevance. Negative transfer alleviated. We design a deep learning framework for human activity recognition. Abstract: Few-shot learning is a technique to learn a model with a very small amount of labeled training data by transferring knowledge from relevant tasks. In this paper, a few-shot learning method for wearable sensor based human activity recognition, which is a technique that seeks high-level human activity knowledge from low-level sensor inputs, is proposed. Due to the high costs to obtain human generated activity data and the ubiquitous similarities between activity modes, it can be more efficient to borrow information from existing activity recognition models than to collect more data to train a new model from scratch when only a few data are available for model training. The proposed few-shot human activity recognition method leverages a deep learning model for feature extraction and classification while knowledge transfer is performed in the manner of model parameter transfer. In order to alleviate negative transfer, a metric is proposed to measure cross-domain class-wise relevance so that knowledge of higher relevance is assigned larger weights during knowledge transfer. Promising results in extensive experiments show the advantages of the proposed approach.